1970
DOI: 10.1364/ao.9.002543
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Atmospheric Turbulence by Narrow Laser Beams

Abstract: In order to determine the characteristic parameters of the atmospheric turbulence, the mutual dancing of two parallel narrow laser beams propagating through a turbulent atmosphere has been investigated theoretically and experimentally. The experiments have been carried out with a He-Ne laser on a 130-m path, one meter from the ground. The method allowed the determination of the variance of the refractive index fluctuations, as well as the values of scale of the turbulence in the vertical and horizontal planes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…According to optical propagation theory (Rao, 2012;Tatarskii, 1961), the scattering is associated with the real part of the atmospheric refractive index, and the absorption is associated with the imaginary part. Based on the relationship between the light intensity fluctuations in the receiving plane after propagation for some distance and the fluctuations of the real part of the atmospheric refractive index (Clifford, 1971;De Bruin and Evans, 2012;Wang et al, 1978), the real part of the atmospheric refractive index structure parameter (ARISP) can be deduced. Under the free-convection condition, the real part of the ARISP is related to the turbulent transport of temperature and water vapour (Wyngaard et al, 1971), which allows a large-aperture scintillometer (LAS) to determine the sensible heat flux and latent heat flux by measuring light intensity fluctuations (Andreas, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to optical propagation theory (Rao, 2012;Tatarskii, 1961), the scattering is associated with the real part of the atmospheric refractive index, and the absorption is associated with the imaginary part. Based on the relationship between the light intensity fluctuations in the receiving plane after propagation for some distance and the fluctuations of the real part of the atmospheric refractive index (Clifford, 1971;De Bruin and Evans, 2012;Wang et al, 1978), the real part of the atmospheric refractive index structure parameter (ARISP) can be deduced. Under the free-convection condition, the real part of the ARISP is related to the turbulent transport of temperature and water vapour (Wyngaard et al, 1971), which allows a large-aperture scintillometer (LAS) to determine the sensible heat flux and latent heat flux by measuring light intensity fluctuations (Andreas, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Although some measurements have revealed that the turbulence often shows anisotropic characteristics (Consortini et al, 1970;Yuan et al, 2014), the isotropic turbulence assumption will still be used in this paper due to the rather high measurement level (this will be further discussed in Sect. 3.1).…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropy of turbulence was previously measured in a number of campaigns [9][10][11][12][13][14][15]. According to these results, the typical correlation width of turbulence fluctuations is generally wider in the horizontal direction and is narrower in vertical.…”
mentioning
confidence: 99%
“…1, the schematic diagram of a beam trespassing the anisotropic turbulence along the horizontal direction is given. Since the anisotropic atmosphere can be considered as a continuum of turbulent eddies all having larger radii in horizontal, x-direction and smaller radii in vertical, y-direction, forming anisotropy ellipse (see also [9]) it appears reasonable to conjecture that the beam will be spread more in the vertical rather than in the horizontal direction. Hence at each point, the intensities along x and y directions will become different with distance, leading to changes in polarization.…”
mentioning
confidence: 99%
See 1 more Smart Citation